A hybrid quantitative approach for assessment of geotechnical hazards in rock tunnels using finite element and variation coefficient methods - Sasan Ghorbani (Scientific Reports)
Abstract Due to the uncertainty ​​of geomechanical parameters, it is necessary to investigate the risks arising from geotechnical hazards in tunnel design from a statistical perspective. In this study, a hybrid quantitative approach incorporating uncertainty in geomechanical parameters, the finite element method (FEM), and the variation coefficient method (VCM) was employed to investigate geotechnical hazards in the Alborz tunnel. At first, by considering five statistical intervals [µ, µ + 0.5(SD), µ-0.5(SD), µ + SD, and µ-SD], different values ​​of geomechanical parameters including uniaxial compressive strength of intact rock, density, depth, Young’s modulus and tensile strength of rock mass, cohesion, friction angle, and in situ stress ratio were generated for three formations of the tunnel. Next, five numerical simulations were performed for each formation using the finite element method. The outputs of the FEM analysis, including the maximum displacement, the maximum axial force in the support systems, and the major principal stress around the tunnel, were used to calculate the three geotechnical hazards namely squeezing potential, seismic activity effects, and stress concentration around the tunnel. The results showed that the vulnerability index for squeezing potential has the highest value in each geological formation. The results of this study and the presented approach can be used as a hybrid model for investigating and predicting hazards in rock tunnels. Additionally, this approach reduces the negative impact of uncertainty in geomechanical parameters on safe and economical design in underground spaces.